Pemeriksaan Hb Gratis Bagi Ibu Hamil Untuk Mencegah Terjadinya Anemia Di Desa Aikmel Utara Kecamatan Aikmel - Baiq Saidatina Hopipah; Huraiza Mahmudah (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2025)
Regularly checking hemoglobin (HB) levels in pregnant women is very important to prevent the risk of anemia which can have an impact on the health of the mother and fetus. Hemoglobin (HB) is a protein found in red blood cells which functions to transport oxygen from the lungs to all body tissues and helps transport carbon dioxide back to the lungs. The main work program of the Real Work Lecture (KKN) group in the form of Free HB Checks for Pregnant Women aims to increase understanding of the importance of routine health checks, especially regarding hemoglobin levels and preventing anemia. This activity was carried out on January 16 2025 in the North Aikmel Village Office Hall with a total of 20 participants, involving 15 pregnant women and representatives from the village forum, PKK and KPM.